Settling process of cassava starch using natural coagulant from Moringa oleifera Lam seed extract (Research, Society and Development, 2020)
Cassava starch has many known applications in food, paper, glue and textile industries, including even biodegradable packaging. In small and medium industries, the starch is obtained by washing the peeled and grinded manioc roots, followed by leaving the washwater for settling before drying the concentrated slurry. Since starch particles are very fine and have a low density, their settling time is high, resulting in a batch operation that lasts for 18 to 24 h. Therefore, it becomes suitable to form larger and heavier starch sets by means of applying coagulants, allowing the particles to settle faster. In the work reported here, the natural coagulant M. oleifera seed extract was used to decrease the settling time of the cassava starch. The effect of the initial concentration of the particles and the coagulant content on the final sedimentation time was evaluated on the batch settling tests. The results showed that the use of the coagulant reduced the sedimentation time in a beaker from 14h to 2h, allowing a quick batch operation.